ISCHEMIA Trial and the Significance of MI - Eduardo A Arias (Radcliffe Medical Media, 2020)
During the past decade, the treatment of choice for chronic coronary syndromes (CCS) has been a contentious issue. Whether revascularisation, either percutaneous or surgical, or optimal medical therapy, offers better prognosis in terms of mortality, MI, and symptom relief, has yet to be confirmed. The long-awaited and recently published International Study of Comparative Health Effectiveness with Medical and Invasive Approaches (ISCHEMIA) trial randomised more than 5,000 patients into a revascularisation plus optimal medical therapy group and an optimal medical therapy alone group. The authors analyse the trial, with particular emphasis on the incidence of MI. They propose a patient-centred approach to incorporate the results of the ISCHEMIA trial into daily practice and determine the best treatment strategy for patients with CCS.